3D Printing Technology in Planning Thumb Reconstructions with Second Toe Transplant. Issue 2 (9th June 2017) - Zang, Cheng‐wu; Zhang, Jian‐lei; Meng, Ze‐zu; Liu, Lin‐feng; Zhang, Wen‐zhi; Chen, Yong‐xiang; Cong, Rui
Abstract : Objective: To report preoperative planning using 3D printing to plan thumb reconstructions with second toe transplant. Methods: Between December 2013 and October 2015, the thumbs of five patients with grade 3 thumb defects were reconstructed using a wrap‐around flap and second toe transplant aided by 3D printing technology. CT scans of hands and feet were analyzed using Boholo surgical simulator software (www.boholo.com ). This allowed for the creation of a mirror image of the healthy thumb using the uninjured thumb. Using 3D images of the reconstructed thumb, a model of the big toe and the second toe was created to understand the dimensions of the donor site. This model was also used to repair the donor site defect by designing appropriate iliac bone and superficial circumflex iliac artery flaps. The polylactic acid model of the donor toes and reconstructed thumb was produced using 3D printing. Surgically, the wrap‐around flap of the first dorsal metatarsal artery and vein combined with the joint and bone of the second toe was based upon the model donor site. Sensation was reconstructed by anastomosing the dorsal nerve of the foot and the plantar digital nerve of the great toe. Patients commenced exercises 2 weeks after surgery. Results: All reconstructed thumbs survived, although partial flap necrosis occurred in one case. This was managed with regular dressing changes. Patients were followed up for 3–15 months. The lengths of the reconstructed thumbs are 34–49 mm. The widths of the thumb nail beds are 16–19 mm, and the thickness of the digital pulp is 16–20 mm. The thumb opposition function was 0–1.5 cm; the extension angle was 5°–20° (mean, 16°), and the angle of flexion was 38°–55° (mean, 47°). Two‐point discrimination was 9–11 mm (mean, 9.6 mm). The reconstructed thumbs had good appearance, function and sensation. Based on the criteria set forth by the Standard on Approval of Reconstructed Thumb and Finger Functional Assessment of the Chinese Medical Association, the results were considered excellent for four cases and good for one case. The success rate was 100%. Conclusions: When planning a wrap‐around flap and second toe transplant to reconstruct a thumb, both the donor and recipient sites can be modeled using 3D printing. This can shorten the operative time by supplying digital and accurate schematics for the operation. It can also optimize the function and appearance of the reconstructed thumb while minimizing damage to the donor site.